Kinetic model of TBP auto-regulation exhibits bistability - Gokhale, Sucheta A.; Roshan, Reema; Khetan, Vivek; Pillai, Beena; Gadgil, Chetan J. (Biology Direct, 2010)
Background: TATA Binding Protein (TBP) is required for transcription initiation by all three eukaryotic RNA polymerases. It participates in transcriptional initiation at the majority of eukaryotic gene promoters, either by direct association to the TATA box upstream of the transcription start site or by indirectly localizing to the promoter through other proteins. TBP exists in solution in a dimeric form but binds to DNA as a monomer. Here, we present the first mathematical model for auto-catalytic TBP expression and use it to study the role of dimerization in maintaining the steady state TBP level. Results: We show that the autogenous regulation of TBP results in a system that is capable of exhibiting three steady states: an unstable low TBP state, one stable state corresponding to a physiological TBP concentration, and another stable steady state corresponding to unviable cells where no TBP is expressed. Our model predicts that a basal level of TBP is required to establish the transcription of the TBP gene, and hence for cell viability. It also predicts that, for the condition corresponding to a typical mammalian cell, the high-TBP state and cell viability is sensitive to variation in DNA binding strength. We use the model to explore the effect of the dimer in buffering the response to changes in TBP levels, and show that for some physiological conditions the dimer is not important in buffering against perturbations. Conclusions: Results on the necessity of a minimum basal TBP level support the in vivo observations that TBP is maternally inherited, providing the small amount of TBP required to establish its ubiquitous expression. The model shows that the system is sensitive to variations in parameters indicating that it is vulnerable to mutations in TBP. A reduction in TBP-DNA binding constant can lead the system to a regime where the unviable state is the only steady state. Contrary to the current hypotheses, we show that under some physiological conditions the dimer is not very important in restoring the system to steady state. This model demonstrates the use of mathematical modelling to investigate system behaviour and generate hypotheses governing the dynamics of such nonlinear biological systems.

Regulation of BACE1 by miR-29a/b in a cellular model of spinocerebellar ataxia 17 - Roshan, Reema; Ghosh, Tanay; Gadgil, Mugdha; Pillai, Beena (RNA Biology, 2012)
Polyglutamine diseases are a class of neurodegenerative disorders characterized by expansion of polyglutamine repeats, protein aggregation and neuronal cell death in specific regions of the brain. The expansion of a polyglutamine repeat in the TATA binding protein (TBP) causes a neurodegenerative disease, Spinocerebellar Ataxia 17 (SC A17). This disease is characterized by intranuclear protein aggregates and selective loss of cerebellar neurons, including Purkinje cells. MicroRNAs are small, endogenous, regulatory non-coding RNA molecules that bind to mRNAs with partial complementarity and interfere in their expression. Here, we used a cellular model of SC A17 where we expressed TBP with 16 (normal) or 59 (pathogenic) polyglutamines and found differential expression of several microRNAs. Specifically, we found two microRNAs, miR-29a/b, were downregulated. With miR-29a/b downregulation, we found an increased expression of targets of miR-29a/b-beta-site amyloid precursor protein cleaving enzyme 1 (BACE 1), p53 upregulated modulator of apoptosis (PUMA) and BAK, increased cytochrome c release and apoptosis. Restoration of miR-29a/b in the pathogenic polyglutamine background reduced the BACE 1 expression. While, antagomiRs against miR-29a/b resulted in an increase in BACE 1 levels and neuronal apoptosis. In spite of the elevation of BACE 1 in Alzhemiers disease, its role in neuronal cell death has not been established. Here, we show that increased BACE 1 expression is not sufficient to cause apoptosis. However restoring level of BACE 1 to normal in polyglutamine cells partially reduced neuronal apoptosis. We show a role for the miR-29a/b-BACE 1 regulatory interaction in SC A17, suggesting that this microRNA could be part of a common molecular mechanism leading to neuronal cell death in multiple neurodegenerative disorders. The identification of a common mechanism of microRNA mediated neurodegeneration not only improves our understanding of the process, but also provides promising and novel therapeutic targets.
Keywords: BACE1; miR-29a/b; neurodegeneration; SCA17; TBP